THE SYNERGY OF INDIVIDUAL CAPACITY AND ORGANIZATIONAL SUPPORT IN LECTURER CAREER DEVELOPMENT - Hariyanto T. Huntua; Sastro M. Wantu; Sukarman Kamuli; Udin Hamim; Yanti Aneta (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2026)
This study aims to analyze the synergy between individual capacity and organizational support in lecturer career development at private higher education institutions. A qualitative approach was employed, with data collected through in-depth interviews, observation, and documentation. The findings reveal that individual capacity comprising academic competence, intrinsic motivation, and personality characteristics plays a significant role in promoting lecturer career development. However, such capacity cannot be optimized without adequate organizational support, including a conducive academic culture, supportive leadership, and a structured career management system. The lack of synergy between individual and organizational factors is identified as one of the main causes of career stagnation. Therefore, lecturer career development requires an integrative approach that combines strengthening individual capacity with continuous institutional improvement. Keywords: career development, lecturers, individual capacity, organizational support, higher education